2020
DOI: 10.1039/d0ce00068j
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry and growth mechanism of highly oriented, single crystalline Nb-doped TiO2 nanorods

Abstract: The effect of the Nb doping on morphological changes in TiO2 nanorods by hydrothermal growth and its enhanced carrier transport were investigated. The nanorod diameter, film thickness, nucleation density, and photocurrent are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The Nb 3d region showed two components with binding energy maxima located at 207.4 ± 0.1 and 210.1 eV ± 0.1 eV that can be assigned to the Nb 3d 5/2 and Nb3d 3/2 core level binding energies. These energy values, along with the spin–orbit separation of 2.7 ± 0.1 eV, are in good agreement with those reported for Nb­(V) sites in Nb 2 O 5 . , In addition, no feature can be observed in the 204–200 eV range, ruling out the presence of any Nb­(II) or Nb(0) species . Furthermore, the O 1s spectrum exhibits a main feature at 532.6 ± 0.1 eV, which can be attributed to the lattice oxygen O 2– in silica, and two minor ones at 530.3 ± 0.1 eV and 533.6 ± 0.1 eV, which can be attributed to the lattice oxygen O 2– in niobium oxide and O–C species, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The Nb 3d region showed two components with binding energy maxima located at 207.4 ± 0.1 and 210.1 eV ± 0.1 eV that can be assigned to the Nb 3d 5/2 and Nb3d 3/2 core level binding energies. These energy values, along with the spin–orbit separation of 2.7 ± 0.1 eV, are in good agreement with those reported for Nb­(V) sites in Nb 2 O 5 . , In addition, no feature can be observed in the 204–200 eV range, ruling out the presence of any Nb­(II) or Nb(0) species . Furthermore, the O 1s spectrum exhibits a main feature at 532.6 ± 0.1 eV, which can be attributed to the lattice oxygen O 2– in silica, and two minor ones at 530.3 ± 0.1 eV and 533.6 ± 0.1 eV, which can be attributed to the lattice oxygen O 2– in niobium oxide and O–C species, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…indicating the successful incorporation of Ta 5+ in TiO 2 [37,38]. Likewise, the characteristic peaks at 207.1 and 209.9 eV for Nb 3d 5/2 and Nb 3d 3/2 in figure 3(d) demonstrate the implantation of Nb 5+ in TiO 2 [39,40].…”
Section: Resultsmentioning
confidence: 73%
“…Investigations revealed that the construction of suitable Ti-based nanostructures (nanorods, 6,7 nanosheets, 8 and nanoflowers 9 ) could promote optical absorption and provide more active sites for oxygen evolution. These structures could be synthesized by the hydrothermal method, 6 sol−gel method, 10 spray pyrolysis method, and so forth. 11 Especially, one-dimensional TiO 2 nanotubes prepared by anodization, characterized by easy recycling, possess a high specific surface area and unidirectional electron transmission channels.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that modified TiO 2 through reasonable physical and/or chemical strategies could improve the PEC performance to some extent. Investigations revealed that the construction of suitable Ti-based nanostructures (nanorods, , nanosheets, and nanoflowers) could promote optical absorption and provide more active sites for oxygen evolution. These structures could be synthesized by the hydrothermal method, sol–gel method, spray pyrolysis method, and so forth .…”
Section: Introductionmentioning
confidence: 99%